Caminhos e descaminhos com a Sequência Fedathi para a construção da expertise do docente fedathiano - Faustino, José Airton de Oliveira (2022)
Teachers, especially those who teach the subject of Mathematics, have experienced difficulties in finding a teaching methodology that can effectively guide their classroom practice. These teachers often take as their teaching method the practice of their old teachers, usually based on repetitions and applications of exercises. With this, few changes are seen in the educational field, however, students are increasingly feeling the need for a different class that is not based on repetition, but on the construction of knowledge. For this reason, the subject of this research sought to know the Fedathi Sequence methodology and apply it as a teaching methodology in his didactic sessions, however, in doing so, he committed some failures in its execution. For this reason, the objective was to get to know the teaching path taken in the application of the Fedathi Sequence, highlighting, through mistakes and successes, how the teacher can apply, with expertise, the Fedathi Sequence as a teaching methodology. In addition, a position of the teacher with expertise in the application of this teaching methodology and the elementary notions that favor a satisfactory application of the Fedathi Sequence will be presented. This work was carried out by means of an exploratory and descriptive methodology, presenting the posture of an expert teacher in the application of the Fedathi Sequence and comparing it with the teaching practice of a teacher with little experience in the use of the Fedathi Sequence. In these classes, both applied the Fedathi Sequence, having as base content the Simple Permutations. Thus, it can be concluded that for a good execution of a didactic session, based on the Fedathi sequence, both the teacher and the students must be immersed in this methodology. For future researches, the challenge remains to appreciate this teaching path for a longer period of time, so that you can understand the stages of evolution of a teacher who uses the Fedathi Sequence as a teaching methodology.